2014
DOI: 10.1007/s00221-014-4122-7
|View full text |Cite
|
Sign up to set email alerts
|

Intended rather than actual movement velocity determines the latency of anticipatory postural adjustments

Abstract: The literature reports that anticipatory postural adjustments (APAs) are programmed according to movement velocity. However, the linkage between APAs and velocity has been highlighted within single subjects who were asked to voluntarily change movement velocity; therefore, till now, it has been impossible to discern whether the key factor determining APA latency was the intended movement velocity or the actual one. Aim of this study was to distinguish between these two factors. We analyzed the APA chain that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
1
16
0
Order By: Relevance
“…Another proof that intra-limb APAs adapt to changes in the postural context within few trials comes from Bruttini et al ( 2014 ) who illustrated that when tapping with the right index-finger, intra-limb APAs were deeply reduced (Figures 2A,B ) if the right forearm was fixated at the wrist, i.e., closer to the voluntary moving segment. Moreover, Esposti et al ( 2015 ) confirmed that also the intra-limb APAs adapt to changes in movement speed (Figure 2C ).…”
Section: Shared Behavioral Properties Of Inter and Intra-limb Apasmentioning
confidence: 69%
See 3 more Smart Citations
“…Another proof that intra-limb APAs adapt to changes in the postural context within few trials comes from Bruttini et al ( 2014 ) who illustrated that when tapping with the right index-finger, intra-limb APAs were deeply reduced (Figures 2A,B ) if the right forearm was fixated at the wrist, i.e., closer to the voluntary moving segment. Moreover, Esposti et al ( 2015 ) confirmed that also the intra-limb APAs adapt to changes in movement speed (Figure 2C ).…”
Section: Shared Behavioral Properties Of Inter and Intra-limb Apasmentioning
confidence: 69%
“…Finally, Berrigan et al ( 2006 ) reported that when pointing is performed towards small targets (i.e., under high accuracy constraints) from an unstable position (i.e., standing vs. sitting), slowing movement speed represents a strategy to reduce the equilibrium disturbance and the associated APAs. However, the above results might simply be an outcome of the relationship between APAs and intended movement speed (Shiratori and Aruin, 2007 ; Esposti et al, 2015 ), given the well known inverse relation (Fitts, 1954 law) between target width and movement speed. In order to get rid of such possible bias, Caronni et al ( 2013 ) studied inter-limb APAs during an upper limb pointing movement toward a target of fixed dimension, while wearing (or not) prismatic lenses, which shift the binocular eye field and make the subject to miss the target (Redding et al, 2005 ).…”
Section: Apa and Precisionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our recent works provided evidence that APAs are programmed with the prime mover recruitment as a shared motor command (Caronni et al, 2013;Bruttini et al, 2014;Esposti et al, 2015). However the ability of the CNS to selectively adjust the APA to changes in the postural context, like adding or removing a fixation point, without affecting the prime mover recruitment (e.g.…”
Section: Introductionmentioning
confidence: 98%